Flowers of the Western Himalayas - Dang, Rupin (New Delhi Wilderness Films India, 1998)
A concise field guide, with introductory comments on environmental factors governing floral diversity and composition, flower-hunting in the region, and an overview of the Himalayas in general. Each species is illustrated with a colour photo, and the text provides details of the altitude at which the plant grows, time of year of flowering, and description.
Keywords: Wild flowers; Himalaya Mountains